Bach2-deficient mice are prone to autoimmune pancreatitis but protected from high-fat diet-induced fatty liver disease - Ehlers, Luise; Kasprick, Anika; Agrifoglio, Ottavia; Gross, Natalie; Ernst, Nancy; Barbosa Gulde, Alanis; Osterloh, Colin; Brauckmann, Noa Linn; Fischer, Nicole Y.; Bergmann-Ewert, Wendy; Ludwig, Ralf J.; Bieber, Katja; et al. (Frontiers in Immunology, 2025)
BackgroundAutoimmune pancreatitis (AIP) is a multifactorial disease caused by both genetic and environmental factors. Previous studies have implicated Bach2, a key regulator of adaptive immunity, in the pathogenesis of this disease. However, direct experimental evidence is lacking. Here, we used C57BL/6N mice with a targeted deletion of Bach2 (Bach2 knockout mice) to study their susceptibility to AIP under homeostatic conditions and in response to two AIP triggers: a high-fat diet (HFD) and polyinosinic:polycytidylic acid (poly I:C).MethodsIn this multicenter preclinical study, Bach2 wild type and knockout mice were maintained under homeostatic conditions, challenged with a HFD for 3 months, or treated with poly I:C for 6 weeks. The pancreata were examined histopathologically. Additionally, RNA sequencing and PamGene multiplex kinase activation measurements were performed. To assess the effects of the HFD, the livers were evaluated for the presence of fatty liver disease.ResultsConsistent with the results of previous studies, Bach2 knockout mice showed reduced growth and developed eosinophilic crystalline pneumonia, necessitating humane euthanasia at the age of 18 weeks. At 8 and 18 weeks of age, pancreatic infiltrates with lymphocytes typical of AIP were frequently detected in Bach2 knockout mice but not in wild type animals without additional manipulations. RNA sequencing analyses and kinase activity assays revealed the activation of processes linked to adaptive immunity in the pancreatic tissues of Bach2 knockout mice. Wild type mice treated with poly I:C showed lymphocytic infiltrates similar to those of untreated knockout mice, whereas HFD did not induce AIP. In Bach2 knockout mice, HFD and poly I:C did not further enhance the disease. As expected, HFD-fed wild type mice developed fatty liver disease. Strikingly, the livers of Bach2 knockout mice were almost free of fat and histological changes, such as hepatocyte ballooning and degeneration. The data obtained from the two project sites were highly consistent, indicating strong intersite reproducibility.ConclusionBach2-deficient C57BL/6N mice were prone to spontaneous AIP development. This could be due to disturbed immune homeostasis with dysregulated activation of adaptive immune system cells. The protective effect of Bach2 deficiency against the development of fatty liver disease warrants further investigation.